The correlation between knowledge and behavior of reading composition label of packaged food on public 2 JHS and Giovani JHS students in Kupang - Maria Sophiana Susi Making; Kristian Ratu; Christina Olly Lada (World Nutrition Journal, 2023)
Background: Labels of packaged foods are used as guidelines for buying packaged food products. School students are a group at high risk to get illness through ingested food. Most of the snacks they consume contain flavorings and some chemicals which are certainly not good for their health. Objective: To determine the relation between knowledge and behavior of reading the packaged food label composition on JHS students in Kupang. Methods: This is an observational analytical study with a cross sectional design conducted at two schools located in Kupang City. 350 subjects were used in this study and divided into Group A consisting of 175 Public JHS students and Group B consisting of 175 Giovanni JHS students, using a google form questionnaire. The respondents were chosen by cluster random sampling technique. This study was analyzed bivariately using the Spearman correlation test. Result: A total of 172 (98.3%) students of Public and Giovanni JHS have very good knowledge about reading the packaged food label composition. A total of 169 (96.5%) students of Public JHS have very good behavior of reading the packaged food label composition and a total of 99 (56.5%) students of Giovanni JHS have good behavior of reading the packaged food label composition. Conclusion: There is a significant correlation (p = 0.004) between knowledge and behavior of reading the packaged food label composition on Public JHS students and there is also a significant correlation (p = 0.046) between knowledge and behavior of reading the packaged food label composition on Giovanni JHS students in Kupang.